Towards Sustainable Computer-assisted Legal Research in Nigerian Law Faculties: Exploring the Nexus between User Education, Intrinsic Motivation and Use of Electronic Law Databases. (January 2019) - Ajala, Anuoluwa Maria
Despite the inclusion of legal research in academic curriculum of law programmes in universities, some factors are still capable of militating against the acquisition of legal research skills by law students. Every law faculty in Nigeria teaches legal research skills to their students, but there are still signs of poor legal research skills by law graduates in Nigeria, which is reflected in their inability to find the legal information that is relevant in the practice of the legal profession. It is argued that computer-assisted legal research entails a process in which electronic law information resources are indispensable. One of the electronic law information resources is the electronic law database. The use of electronic law databases is indeed crucial to legal research. However, lack of user education may lead to lack of intrinsic motivation to use electronic databases. In Nigerian law faculties, a lot of funds are invested in provision of electronic information resources in order to promote legal research among law students. However, the relationship between user education and use of electronic law databases may or may not justify the funds invested. This article explicates the place of computer-assisted legal research in law faculties and reveals that there is a need for law students to be intrinsically motivated to use electronic law databases. This article also exhibits additional measures that Nigerian law faculties can take in order to motivate law students to use the electronic law databases.